2017
DOI: 10.1002/brb3.867
|View full text |Cite
|
Sign up to set email alerts
|

Serum sodium and chloride are inversely associated with dyskinesia in Parkinson's disease patients

Abstract: ObjectiveWe aim to report and evaluate the associations between serum sodium and chloride and dyskinesia in patients with Parkinson's disease. One hundred and two patients with Parkinson's disease were enrolled in this study.MethodsPatients’ serum electrolytes including sodium, calcium, potassium, magnesium, and chloride were measured. Other demographic information was collected, and Unified Parkinson's disease rating scale and Hoehn and Yahr stage scale were also performed.ResultsPatients with dyskinesia tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…This is in agreement with a recent study, as increased salt intake reduced the Lactobacillus in mice model 62 . Furthermore, serum sodium levels are inversely associated with dyskinesia in Parkinson’s disease patients as lower levels of serum sodium are more likely to have dyskinesia 63 . Nevertheless, further understanding the physiology of ion channels and the gut microbiome would be helpful to understand gut-related onset of PD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with a recent study, as increased salt intake reduced the Lactobacillus in mice model 62 . Furthermore, serum sodium levels are inversely associated with dyskinesia in Parkinson’s disease patients as lower levels of serum sodium are more likely to have dyskinesia 63 . Nevertheless, further understanding the physiology of ion channels and the gut microbiome would be helpful to understand gut-related onset of PD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies with small sample populations showed a highly significant relationship between serum sodium and NCV [11]. Low extracellular sodium had an adverse effect on nerve cells, such as osmotic demyelination [12], and was associated with dyskinesia in patients with Parkinson's [13]. In addition, excessive sodium intake highly correlated with macular edema in patients with type 1 diabetes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Osmotic edema can also increase neuronal excitability through the activation of N-methyl-daspartate receptors [34], which may accelerate the development of dyskinesia [35]. Another study clarified that the serum sodium level was inversely associated with dyskinesia in patients with Parkinson's disease [13]. Currently, no studies correlating the serum sodium level with DPN in patients with type 2 diabetes mellitus are available.…”
mentioning
confidence: 99%
“…It has been reported that the death of dopaminergic neurons might be closely related to the hypochlorite-dependent conversionmediated oxidative stress process. 4 As a consequence, quantitative investigations in terms of the correlation of cerebral Cl − concentrations with the progress of PD are highly desirable for better studying the specific pathogenesis of this disease. In this case, developing a facile and accurate platform for in vivo measurement of cerebral Cl − is really urgent.…”
mentioning
confidence: 99%
“…Chloride ion (Cl – ) plays a vital role in maintaining the normal physiological functions of the human body, and there is accumulating evidence indicating that the dysregulation of Cl – levels is implicated in some psychiatric and neurological disorders. As the second-most encountered neurodegenerative disease, Parkinson’s disease (PD) is mainly featured with increased death of dopaminergic neurons. It has been reported that the death of dopaminergic neurons might be closely related to the hypochlorite-dependent conversion-mediated oxidative stress process . As a consequence, quantitative investigations in terms of the correlation of cerebral Cl – concentrations with the progress of PD are highly desirable for better studying the specific pathogenesis of this disease.…”
mentioning
confidence: 99%